Emotional Public Opinion and Its Indirect Influence on Americans’ Policy Support During the 2022 Russian Invasion of Ukraine - Lu, Hang (SAGE open, 2025)
This study investigates how poll-based emotion consensus messaging influences American support for various policies during the 2022 Russian invasion of Ukraine, with an aim to unpack the cognitive-emotional mechanisms behind this influence. Employing a between-subjects factorial experiment with a national sample of U.S. adults (N = 1,087), the research method involved randomly assigning participants to one of five consensus message conditions: seriousness, anger, sadness, anxiety, or control. The results demonstrated that emotion consensus messaging indirectly influenced policy support through a sequential process: first, by shaping perceived emotion consensus, and then by altering individual emotional responses. Specifically, anger consensus messaging increased support for punitive policies, sadness for humanitarian aid, and anxiety for risk-averse options like concessions. In line with the heuristic-systematic model, this study revealed that the influence of consensus messaging was moderated by perceived issue importance, with significant effects observed primarily among participants who considered the issue to be of low importance. This study concludes that poll-based emotion consensus messaging can indirectly shape public policy support, particularly when the issue at hand is not deemed critical by the audience.